2023
DOI: 10.3390/su15032452
|View full text |Cite
|
Sign up to set email alerts
|

Species-Specific Secondary Metabolites from Primula veris subsp. veris Obtained In Vitro Adventitious Root Cultures: An Alternative for Sustainable Production

Abstract: Primula veris subsp. veris L. is a perennial herbaceous and medicinal plant species the roots and flowers of which are a source of valuable pharmaceutical raw materials. The plant tissues are used to produce expectorant and diuretic drugs due to their high content of triterpene saponins and phenolic glycosides. Underground roots of P. veris can be obtained only through a destructive process during the plant’s harvesting. In the present study, an in vitro adventitious root production protocol was developed as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The production of natural products is important for functional research and commercial development ( 42 ). But, for the vast majority of natural products, it is the most important factor which limits their further development and research due to their low content in plant tissues and the long growth cycle of plants ( 43 ).…”
Section: Resultsmentioning
confidence: 99%
“…The production of natural products is important for functional research and commercial development ( 42 ). But, for the vast majority of natural products, it is the most important factor which limits their further development and research due to their low content in plant tissues and the long growth cycle of plants ( 43 ).…”
Section: Resultsmentioning
confidence: 99%
“…These studies demonstrated that auxin can be used to establish in vitro root culture for phytochemical production, but the appropriate type and concentration of auxin for pokeweeds need to be studied. Additionally, root induction in liquid medium can promote root growth and the production of phytochemicals due to better nutrient circulation than solid medium [ 26 , 27 ]. Therefore, this study established appropriate medium states and plant growth regulators (PGRs) for in vitro pokeweed adventitious root induction from leaf explants, considering root growth and phytochemical parameters.…”
Section: Introductionmentioning
confidence: 99%
“…veris at the Hellenic Agricultural Organization-Demeter in 2020 [ 25 ], following an optimized protocol for the micropropagation of cowslip via shoot tip explants derived from seedlings, in order to facilitate the mass production of plants and the sustainable cultivation of the plant species. This approach has also been followed by the cultivation of roots [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%